Efektivitas Permodalan Nasional Madani Membina Ekonomi Keluarga Sejahtera (PNM MEKAAR) dalam Memenuhi Kebutuhan Sosial Ekonomi Keluarga di Kelurahan Sitinjak - Nadya Putri Siregar; Berlianti Berlianti (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
Poverty reduction in Indonesia is supported by economic activity and social assistance programs, the government provides business capital loans so that people do not depend on social assistance. One of them is PNM Mekaar which aims to develop and empower MSMEs in order to improve the economy and improve the welfare of program implementers, namely underprivileged women. However, problems occur in the implementation of this program, such as use of business capital for personal needs and weekly installment bills without training for customers. This study aims to determine the effectiveness of capital provided by PNM Mekaar for socio-economic needs of families in Sitinjak, South Tapanuli. This research uses descriptive qualitative methods so researchers can better understand the problems that occur. Data collection techniques in is interviews, observation, literature study and documentation. The conclusion obtained from the results of this study is that business capital loans provided by PNM Mekaar are not effective in meeting the socio-economic needs of families. Effectiveness can be measured through following 5 indicators: 1). Indicators of program understanding which show that there are customers who do not know about the purpose of Mekaar, 2). Target accuracy shows that there are customers who are not classified as underprivileged, 3). Timeliness shows that there are customers who do not attend group meetings and are delinquent in weekly payment installments, 4). Achievement of goals shows that only customers who have a business that has increased income, the businesses run by customers are in the MSME and Agriculture sectors. 5). Real changes show that customers' personal financial management is not yet good. Meanwhile, the socio-economic needs of the family which include food, clothing, shelter, education, and health can be met even before becoming PNM Mekaar customers.